P43 Real-world experience of subcutaneous vedolizumab for treatment of IBD in NHS tayside. (19th June 2022) - McLean, Mairi; Cartlidge, Peter; Fyall, Julie; Paterson, Jacqueline; Groome, Max; Mowat, Craig; McLean, Mairi H
Abstract : Introduction: Vedolizumab is an anti-integrin biologic therapy for moderate-severe inflammatory bowel disease (IBD). Traditionally this was delivered by intravenous (IV) infusion. The VISIBLE trial demonstrated that subcutaneous (SC) vedolizumab was effective and safe. This also reduced the need for a hospital visit, reducing risk in the COVID-19 pandemic, with a substantial cost saving. Vedolizumab was switched to SC administration in NHS Tayside in October 2020. This study aimed to demonstrate a real-world experience of the use of SC vedolizumab for IBD. Methods: Patients were identified from the IBD biologic database. Caldicott approval was granted for a retrospective analysis of patient data via electronic patient records including patient gender, age, IBD diagnosis and dates for when Vedolizumab was commenced, switched to SC or stopped. Blood markers of inflammation (albumin, platelets, CRP and haemoglobin) 1 month before and 3-6 months after the switch to SC and stool calprotectin were recorded when available. Statistical analysis with Chi Square and Mann Whitney non-parametric tests revealed significance if p<0.05. Results: Seventy-one patients on IV vedolizumab in October 2020 were invited to switch to SC, supported by a nurse led clinic consultation. One patient declined due to needle phobia and 70 (98%) accepted. SC administration was well tolerated with no patients reporting injection difficulties. Eight patients (11%) stopped SC vedolizumab within a 6-month period, 5 (62.6%) due to a flare in IBD and 3 (37.5%) due to side effects (skin reactions, paraesthesia). Thirty patients who remained on this treatment with no issues were compared to the 8 patients who stopped SC vedolizumab to explore whether there was patient or disease characteristics to identify those who failed this therapy. There was no statistically significant difference in patient age (42 years versus 44 years, p=0.5124) or disease phenotype (UC versus CD, p=0.155) between the two groups. of those that stopped SC administration, more were female (75% versus 57%, p=0.007). There was no difference in total duration of vedolizumab therapy between the groups; 19.6 months for those that continued versus 13.6 months for those that stopped, p=0.841. There was no significant difference in albumin, platelets, and haemoglobin reported before or after the switch between the two groups. There was insufficient recording of CRP and calprotectin to allow analysis. Conclusions: SC vedolizumab was accepted, well tolerated and effective in the majority of patients in our centre. There was no blood inflammatory biomarker or demographic signature to identify those who stopped SC therapy due to flare or side effects using standard monitoring.